1997
DOI: 10.1002/(sici)1096-911x(199709)29:3<213::aid-mpo9>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant micronutrients and childhood malignancy during oncological treatment

Abstract: Serum antioxidant vitamins A (retinol) and E (α‐tocopherol), β‐carotene, zinc, and selenium, and cholesterol and related proteins for 170 children with newly diagnosed malignancy were measured at diagnosis and 6 months after initiation of treatment, and compared with those of 632 cancer‐free controls. Incident cancer cases and controls were 1–16 years old and recruited between 1986 and 1989. At diagnosis, age‐ and sex‐adjusted serum concentrations of retinol, β‐carotene, zinc, and α‐tocopherol were significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 12 publications
5
19
1
Order By: Relevance
“…These results were also confirmed by Zuo et al and Unal et al, who found decreased zinc levels in serum of leukemic patients (Zuo et al, 2006) and in serum of Hodgkin's disease patients, respectively (Unal et al, 2001). Moreover, decreased blood levels of antioxidants (i.e., retinol, α-tocopherol, and β-carotene) and zinc were found in childhood malignancies (Malvy et al, 1993(Malvy et al, , 1997, which could be one of the negative effects of zinc-metabolism alterations. Zinc deficiency has also been associated with oxidative stress (OS) (Eide, 2011) and esophageal, head and neck cancer, and prostate and other cancer types, especially in their development and progression (Franklin and Costello, 2007;Hogstrand et al, 2009;Ostrakhovitch, 2011;Fukada et al, 2011;Pedersen et al, 2009).…”
Section: S Krizkova Et Alsupporting
confidence: 75%
“…These results were also confirmed by Zuo et al and Unal et al, who found decreased zinc levels in serum of leukemic patients (Zuo et al, 2006) and in serum of Hodgkin's disease patients, respectively (Unal et al, 2001). Moreover, decreased blood levels of antioxidants (i.e., retinol, α-tocopherol, and β-carotene) and zinc were found in childhood malignancies (Malvy et al, 1993(Malvy et al, , 1997, which could be one of the negative effects of zinc-metabolism alterations. Zinc deficiency has also been associated with oxidative stress (OS) (Eide, 2011) and esophageal, head and neck cancer, and prostate and other cancer types, especially in their development and progression (Franklin and Costello, 2007;Hogstrand et al, 2009;Ostrakhovitch, 2011;Fukada et al, 2011;Pedersen et al, 2009).…”
Section: S Krizkova Et Alsupporting
confidence: 75%
“…[20] In a few studies, although the transferrin level has been reported to be an indicator that accompanies malnutrition, it has been stated that it was not as sensitive as prealbumin. [21] In the present study, 59 (96.7%) of the patients had dysphagia. Fifty-three patients (86.9%) had a history of weight loss while 43 (70.5%) patients had a cachectic appearance.…”
Section: Discussionsupporting
confidence: 47%
“…Moreover, a study that analyzes the oxidative profile in children just diagnosed with ALL in comparison to that of the different stages of treatment has not been found in the literature. Other studies evaluated antioxidant status in children with newly diagnosed ALL and during the first months of chemotherapy [31,32], but not with patients out-of-treatment. In this context, we have examined the activities of antioxidant enzymes (SOD, CAT) as well as thiol, vitamin E and MDA levels and protein carbonylation in the blood of just diagnosed ALL patients as compared to those in the different stages of treatment and after therapy.…”
Section: Discussionmentioning
confidence: 99%